Re-Public: workflow to publish and reuse Linked Open Government Data - Beluzo, José Rodolfo; Dias, Bruno; Craveiro, Gisele Silva; Araujo, Renata (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2021: Anais do XVII Simpósio Brasileiro de Sistemas de Informação, 2021)
Brazilian governments have made progress on transparency - including publishing Open Government Data (OGD). Although there are still gaps to be filled on how to address properly OGD supply and demand. The consumption has been limited by data and metadata quality, heterogeneity, format and data structure. In this paper, we explore the "Re-public" design - a generic process that aims to re-publish OGD in RDF format - based on OWL (Ontology Web Language) ontologies. "Re-public" purpose is to improve data connectivity and availability to consumption - both can be achieved by adding a semantic layer to data. We applied "Re-public" on the government budget field: using Constitucional Transfers to Cities dataset (Transferências Constitucionais para Municípios) and DBpedia open data. The results show that, using "Re-Public", is possible to publish original CSV files in a new format that enables semantic web tools to be used.